Resin composition and molded article
The resin composition, featuring an enzyme carrier with non-covalently adsorbed enzymes, addresses the challenges of controlled decomposition and hydrolysis resistance in biodegradable plastics, ensuring effective biodegradability in marine environments.
Patent Information
- Application Number
- JP2024180595
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-10-17
- Filing Date
- 2024-10-16
- Publication Date
- 2025-04-30
AI Technical Summary
Existing biodegradable plastics face challenges in controlling the onset of decomposition, particularly in marine environments where degradation bacteria are scarce, and they also lack hydrolysis resistance.
A resin composition is developed that includes an enzyme carrier with enzymes adsorbed non-covalently, which maintains stability during use but decomposes when exposed to ionic aqueous solutions, such as seawater.
The resin composition effectively functions as a polymer during normal use while ensuring biodegradability when discarded in marine environments, addressing the issues of controlled decomposition and hydrolysis resistance.
Smart Images

Figure 2025069099000001 
Figure 2025069099000002 
Figure 2025069099000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition and a molded article thereof. More specifically, the present invention relates to a biodegradable resin composition and a molded article thereof. [Background technology]
[0002] In modern society, plastics are used in a wide range of applications in our daily lives, such as packaging materials, home appliance materials, and building materials, due to their light weight, electrical insulation, moldability, and durability. Plastics used for these applications include polyethylene, polypropylene, polystyrene, polyvinyl chloride, and polyethylene terephthalate. However, molded products of these plastics are difficult to decompose in the natural environment, so they tend to remain in the ground even if buried after use. In addition, even if they are incinerated, harmful gases may be generated and damage the incinerator. In recent years, from the perspective of preventing environmental pollution, there has been a worldwide demand for products that can be composted in ordinary households (home compostable products).
[0003] As a means for solving the above problems, research has been conducted on biodegradable materials that can be decomposed into carbon dioxide and water by microorganisms in compost. A representative example of a biodegradable material is polylactic acid (hereinafter sometimes abbreviated as "PLA") (Non-Patent Document 1).
[0004] In recent years, marine pollution caused by plastics dumped in the ocean has become a major social issue. Therefore, if plastics with high marine biodegradability were developed, it would be expected that the problem of marine pollution caused by plastics would be solved. However, the above-mentioned biodegradable plastics have mainly been developed with the focus on biodegradation in compost, and there has been little research on plastics that are highly degradable in seawater, where there are few decomposing bacteria. On the other hand, when using plastics, they are usually required to be resistant to degradation, and it is considered preferable that they have high hydrolysis resistance. Therefore, in practical terms, it is desirable to develop a plastic that is both biodegradable and hydrolysis resistant, but since biodegradability and hydrolysis resistance are mutually exclusive properties in terms of the decomposition of plastics, it has been thought that it is difficult to develop a plastic that has both of these properties.
[0005] In response to this, Non-Patent Document 2 proposes a biodegradable plastic in which an enzyme is embedded in a porous carrier, specifically disclosing a film in which protease K (an enzyme) is physically fixed and captured in beads (holes) in a porous carrier and kneaded into poly(L-lactic acid) (hereinafter sometimes referred to as "PLLA"). Non-Patent Document 2 discloses a technology that maintains the enzyme's decomposition activity by physically fixing and capturing an enzyme that is damaged during thermal kneading when used alone and subsequently does not exhibit decomposition activity on uncharged acrylamide beads (porous carrier) and kneading the enzyme into PLLA (polymer). In this technology, the enzyme starts to work when the porous carrier comes into contact with a buffer solution, initiating the decomposition of PLLA, and it is therefore considered to be useful as a polymer that functions as a polymer during use and decomposes after disposal. [Prior art documents] [Non-patent literature]
[0006] [Non-Patent Document 1] Polymer Degradation and Stability 98 (2013) 1089-1096 [Non-Patent Document 2] Biomacromolecules 2020, 21, 3301-3307 Summary of the Invention [Problem to be solved by the invention]
[0007] In the technique disclosed in Non-Patent Document 2, it is believed that when the film surface is scratched and comes into contact with moisture, enzymes are released and decomposition of PLLA begins. However, the technology disclosed in Non-Patent Document 2 has a problem in that decomposition starts when the porous carrier comes into contact with water even during normal use as a polymer. That is, there is a problem in that it is difficult to control the starting point of decomposition, for example, decomposition starts only when the porous carrier is unintentionally discarded in the ocean and comes into contact with seawater. Therefore, an object of the present invention is to provide a resin composition which exhibits its polymeric function while in use as a molded article or the like, and which initiates decomposition of the polymer when it comes into contact with, for example, seawater after unintentional disposal. [Means for solving the problem]
[0008] In view of the above-mentioned situation, the inventors conducted intensive research and discovered that a resin composition containing an enzyme support in which an enzyme is non-covalently adsorbed to the support and a resin can solve the above-mentioned problems, and thus completed the present invention. That is, the gist of the present invention is as follows.
[0009] [1] A resin composition comprising at least one type of enzyme, at least one type of support, and at least one type of resin, wherein the enzyme is adsorbed to the support by a non-covalent bond. [2] The resin composition according to [1] above, wherein the support has one or more ionic functional groups and contains the enzyme support in which the enzyme is adsorbed onto the support by ionic bonds. [3] The resin composition according to [1] or [2] above, wherein the enzyme carrier is contained in the resin composition in an amount of 0.5% by weight or more and 50% by weight or less. [4] The resin composition according to any one of the above [1] to [3], wherein the support has a cationic functional group. [5] The resin composition according to any one of the above [1] to [4], wherein the support has an ammonium group. [6] The resin composition according to any one of the above [1] to [5], wherein the support is biodegradable. [7] The resin composition according to any one of the above [1] to [6], wherein the enzyme has an isoelectric point of 7.0 or less. [8] The resin composition according to any one of the above [1] to [7], wherein the enzyme is a hydrolase. [9] The resin composition according to the above [8], wherein the hydrolase is an esterase.
[10] The resin composition according to [8] above, wherein the hydrolase is cutinase or lipase.
[11] The resin composition according to any one of the above [1] to
[10] , wherein the support contains a naturally occurring material as a constituent component.
[12] The resin composition according to any one of the above [1] to
[11] , wherein the support contains either cellulose or chitosan.
[13] The resin composition according to any one of the above [1] to
[12] , wherein the resin is a biodegradable resin.
[14] The resin composition according to
[13] above, wherein the biodegradable resin is a polyester resin.
[15] The resin composition according to
[14] above, wherein the polyester resin contains an aliphatic diol unit.
[16] The resin composition according to
[14] or
[15] above, wherein the polyester resin contains an aliphatic dicarboxylic acid unit.
[17] A molded article of the resin composition according to any one of [1] to
[16] above. Effect of the Invention
[0010] According to the present invention, it is possible to provide a resin composition and a molded article thereof which exhibit the function of a polymer during use as a molded article or the like, and which initiates decomposition of the polymer when exposed to an ionic aqueous solution after disposal. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will be described in detail below with reference to the preferred embodiments. The present invention is not limited to the following description, and can be modified as desired without departing from the scope of the present invention. In this specification, when a numerical value or physical property value is enclosed by "~", the value before and after the "~" is included.
[0012] The present invention will be described in detail below. However, the description of the constituent elements described below is one example (representative example) of an embodiment of the present invention, and the present invention is not limited to these contents, and can be implemented in various modifications within the scope of the gist of the present invention.
[0013] [Resin composition] One embodiment of the present invention is a resin composition comprising at least one type of enzyme, at least one type of support, and at least one type of resin, and containing an enzyme support in which the enzyme is adsorbed to the support by a non-covalent bond. The resin composition of the present invention can be a biodegradable resin composition depending on its configuration, and is preferably a biodegradable resin composition. Hereinafter, the resin composition may be referred to as "the present resin composition" including the biodegradable resin composition. In this specification, "biodegradable" means that a resin can be decomposed by the action of microorganisms through hydrolysis or the like into low molecular weight compounds such as oligomers and monomers, and these compounds can be further decomposed into water, carbon dioxide, etc.
[0014] The resin composition of the present invention will be described in detail below, taking the biodegradable resin composition as an example. The resin composition of the present invention may be biodegraded in any environment as long as the resin is biodegradable. In particular, the amount and variety of microorganisms in seawater are small, making it difficult for the resin to be biodegraded. However, the resin composition of the present invention has a biodegradable enzyme that maintains its enzymatic decomposition activity in the resin composition and even in a molded product of the resin composition, so that it can exhibit sufficient biodegradability, for example, in the ocean. That is, the enzyme support contained in the resin composition of the present invention is able to exert its function as a decomposing enzyme by being exposed to an ionic aqueous solution and releasing the enzyme from the enzyme support. On the other hand, before coming into contact with the ionic aqueous solution, the enzyme support maintains the enzyme in an adsorbed state, so the enzyme is not released and the molded article of the resin composition functions as a polymer. As described above, the resin composition of the present invention can promote enzymatic decomposition and biodegradation by containing decomposition enzymes, even in environments where biodegradation is difficult, such as the ocean, so the resin composition of the present invention and its molded body are highly biodegradable even in seawater and are suitable as marine biodegradable resin compositions.
[0015] <Enzyme> The resin composition contains at least one enzyme. The enzyme used in the present resin composition is appropriately determined depending on the type of resin (polymer) to be decomposed and the environment in which the decomposition takes place. Specifically, the type of enzyme is appropriately determined depending on the environment, such as decomposition in soil or in the ocean. In the present invention, hydrolases are preferred. Examples of hydrolases include hydrolases called cutinase, lipase, phospholipase, lysophospholipase, esterase (in the narrow sense), protease, amylase, cellulase, chitinase, peptinase, pectinase, glucoamylase, serine hydrolase, xylanase, etc., depending on the substrate to be hydrolyzed. Enzymes that hydrolyze polyesters are preferably esterases (in the broad sense), which are enzymes that hydrolyze ester bonds, and further include hydrolases called cutinase, lipase, phospholipase, lysophospholipase, esterase (in the narrow sense), etc., depending on the substrate to be decomposed. Two or more of these may be used in combination. Among these enzymes, cutinase, lipase, phospholipase, lysophospholipase, protease, and amylase are preferred, cutinase, lipase, phospholipase, and lysophospholipase are more preferred, and cutinase and lipase are particularly preferred. The above enzyme specifically and rapidly decomposes the ester bonds of polyester resins, and therefore it is possible to decompose the polyester resin in an extremely short time under relatively mild temperature conditions, thereby reducing the strength of the resin to a desired level. In the present invention, the term "esterase" in the broad sense includes lipase, while the term "esterase" in the narrow sense refers to an ester hydrolase that hydrolyzes esters of monohydric alcohols and lower fatty acids.
[0016] <Enzyme carrier> In the resin composition of the present invention, it is important that the enzyme is adsorbed to the support described below by a non-covalent bond to form an enzyme support. Since the non-covalent bond is not as strong as the covalent bond, the bond is easily dissociated by an external stimulus, and the enzyme is released from the support. The released enzyme functions as a decomposing enzyme and decomposes the resin. Here, examples of non-covalent bonds include intermolecular forces, specifically ionic bonds, hydrophobic bonds, hydrogen bonds, van der Waals forces, and bonds due to dipole interactions, but in the present invention, ionic bonds and hydrogen bonds are preferred, and ionic bonds are more preferred. Ionic bonds are not as strong as covalent bonds, so when the enzyme support comes into contact with seawater, they can be more easily dissociated and release the enzyme compared to covalent bonds. On the other hand, under normal use conditions, the enzyme is not released because the enzyme and the support are ionic bonds, and decomposition of the resin by the enzyme does not begin. In addition, because bonds based on hydrogen bonds and van der Waals forces have weaker binding strength than ionic bonds, these bonds can be used to adsorb the enzyme onto the support depending on the purpose, thereby initiating the decomposition of the resin.
[0017] The content of the enzyme carrier in the resin composition of the present invention is usually 0.5% by weight or more, preferably 0.7% by weight or more, more preferably 0.9% by weight or more, even more preferably 1.0% by weight or more, particularly preferably 2.0% by weight or more, and most preferably 3.0% by weight or more, from the viewpoint of releasing a sufficient amount of enzyme and proceeding with the decomposition of the resin well. The upper limit of the enzyme carrier content in the resin composition of the present invention is usually 50.0% by weight or less, preferably 40.0% by weight or less, more preferably 20.0% by weight or less, even more preferably 10.0% by weight or less, particularly preferably 5.0% by weight or less, and most preferably 3.1% by weight or less, from the viewpoint of suppressing the aggregation of the enzyme carrier in the resin composition and improving the mechanical properties of the molded product of the resin composition. The content can be adjusted depending on the application of the molding. The particle size of the enzyme carrier used in the present invention is usually 500 μm or less, preferably 250 μm or less, more preferably 100 μm or less, even more preferably 50 μm or less, and particularly preferably 20 μm or less, from the viewpoints of easy mixing with resin, less occurrence of poor appearance, and easy achievement of the effect of promoting biodegradation. In particular, in order to obtain good mechanical properties and appearance together with the effect of promoting biodegradation, it is preferably 18 μm or less, more preferably 13 μm or less, and even more preferably 10 μm or less. The lower limit is not particularly limited, but from the viewpoint of workability, it is preferably 0.1 μm or more, more preferably 0.5 μm or more, even more preferably 1.0 μm or more, and particularly preferably 3.0 μm or more.
[0018] The enzyme may be anionic or cationic, but is preferably anionic in neutral. That is, the enzyme is preferably one whose isoelectric point (pI) is lower than the pH of the aqueous solution during the adsorption treatment. The pI of the enzyme is preferably 7.0 or less, more preferably 6.0 or less, even more preferably 5.2 or less, and most preferably 5.0 or less. The lower limit of pI is preferably 1.0 or more, more preferably 2.0 or more, even more preferably 3.0 or more, and most preferably 4.0 or more. When the enzyme is anionic, it can be ionically bonded to a cationic support, which will be described later.
[0019] <Support> The resin composition includes at least one support. The support used in the present resin composition is not particularly limited as long as it can support the enzyme, and examples thereof include crosslinkable synthetic polymers such as polyvinyl alcohol polymers, styrene-divinylbenzene polymers, and (meth)acrylic polymers; natural organic polymers such as cellulose, sepharose, agarose, chitosan, and chitin; and inorganic polymers such as silica, glass, ceramics, and clay minerals. These supports can be used after being partially modified to facilitate the adsorption of the enzyme. Since the resin composition of the present invention and its molded article are preferably easily decomposed after disposal or are made of naturally derived components, it is preferable that the support is also biodegradable, and among the above-mentioned polymers, natural organic polymers such as cellulose and chitosan, and inorganic polymers such as silica and clay minerals are more preferable. From the viewpoint of carbon neutrality, the support of the present invention preferably contains naturally occurring materials as constituents, and the above-mentioned natural organic polymers are preferable. Among them, cellulose and chitosan are particularly preferable because they are easily biodegradable in the natural environment. Furthermore, the support in the present invention is preferably a porous body, since the surface area is large and a large amount of the enzyme can be adsorbed into the pores.
[0020] The support according to the present invention preferably has at least one or more ionic functional groups. Furthermore, when a neutral anionic enzyme, which is a preferred embodiment, is used, the support preferably has a cationic functional group in order to form an ionic bond with the anionic enzyme. Examples of the cationic functional group include an ammonium group, a phosphonium group, and a sulfonium group, and among these, an ammonium group is more preferable. Here, the ammonium group refers to a primary to quaternary ammonium group.
[0021] [resin] The resin constituting the resin composition of the present invention is not particularly limited, but is preferably a biodegradable resin, particularly one that exhibits enzymatic biodegradability, such as polyvinyl alcohol (PVA), polyglycolic acid (PGA), polyester resin, polyamide resin, etc. Hereinafter, polyester resin will be described in detail as a representative biodegradable resin.
[0022] <Polyester resin> The resin composition according to the present embodiment preferably contains a polyester resin. The polyester resin contained in the resin composition according to the present embodiment is preferably a biodegradable polyester resin. The biodegradability of the resin and the resin composition will be described later. The polyester resin contained in the resin composition according to the present embodiment may be used alone or in any combination and ratio of two or more polyester resins. As the polyester resin, biodegradable polyester resins such as polylactic acid (PLA), polyhydroxyalkanoate (PHA), poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBH), polycaprolactone (PCL), polybutylene succinate (PBS), polybutylene succinate adipate (PBSA), polybutylene succinate sebacate (PBSSe), polybutylene adipate terephthalate (PBAT), and polybutylene sebacate terephthalate (PBSeT) are preferred. The polyester resin may be used alone or in combination with two or more resins having different types and numbers of constituent units, ratios of constituent units, manufacturing methods, physical properties, etc. Also, resins other than polyester may be used in combination. When resins other than polyester are used in combination, biodegradable resins such as polyvinyl alcohol, polyamide, and polyethylene glycol are preferred.
[0023] The polyester resin contained in the resin composition according to the present embodiment will be described in detail below. Each repeating unit in the polyester resin is also called a compound unit corresponding to the compound from which the repeating unit is derived. For example, a repeating unit derived from an aliphatic diol is also called an "aliphatic diol unit", a repeating unit derived from an aliphatic dicarboxylic acid is also called an "aliphatic dicarboxylic acid unit", and a repeating unit derived from an aromatic dicarboxylic acid is also called an "aromatic dicarboxylic acid unit". In addition, the "main structural unit" in a polyester resin usually refers to a structural unit that is contained in the polyester resin at 80% by weight or more, and also includes cases where no structural unit other than the main structural unit is contained. The polyester resin contained in the resin composition according to the present embodiment is preferably a polyester resin having a diol unit and a dicarboxylic acid unit and an aliphatic oxycarboxylic acid resin, and more preferably a polyester resin having a diol unit and a dicarboxylic acid unit.
[0024] The polyester resin may be an aliphatic polyester resin, an aromatic polyester resin, or an aliphatic-aromatic polyester resin. From the viewpoint of high flexibility, an aliphatic polyester resin or an aliphatic-aromatic polyester resin is preferred, and from the viewpoint of biodegradability, an aliphatic polyester resin is more preferred. In this specification, aromatic also includes heteroaromatic. The polyester resin contained in the resin composition according to this embodiment preferably has two or more types of structural units, and more preferably has two or more types of dicarboxylic acid units, since it is believed that biodegradation is facilitated by a decrease in the crystallinity of the polyester resin and an increase in the amorphous portion.
[0025] (diol unit) The diol unit of the polyester resin may be aliphatic or aromatic. The diol unit of the polyester resin may be one type or two or more types of units in any combination and ratio, and may have aliphatic diol units and aromatic diol units. In terms of easy biodegradation, it is preferable to include an aliphatic diol in the constituent unit, and it is more preferable to have a linear aliphatic diol unit. The diol unit is particularly preferably a diol unit represented by the following general formula (1). -OR 1 -O- (1) In formula (1), R 1 represents an aliphatic hydrocarbon group having 2 to 20 carbon atoms.
[0026] R 1 From the viewpoints of moldability, mechanical strength, etc., the number of carbon atoms in the aliphatic hydrocarbon group represented by the following formula is usually 2 or more, preferably 4 or more, and usually 20 or less, preferably 16 or less, more preferably 13 or less, even more preferably 10 or less, and particularly preferably 6 or less. A particularly preferred aliphatic hydrocarbon group is an aliphatic hydrocarbon group having 4 carbon atoms. Examples of the aliphatic diol that provides the aliphatic diol unit represented by formula (1) include, for example, ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,4-cyclohexanedimethanol, and the like, more preferably 1,4-butanediol, 1,3-propanediol, and ethylene glycol, and particularly preferably 1,4-butanediol.
[0027] The diol unit contained in the polyester resin may have an aromatic diol unit. Specific examples of aromatic diol components that give aromatic diol units include xylylene glycol, 4,4'-dihydroxybiphenyl, 2,2-bis(4'-hydroxyphenyl)propane, 2,2-bis(4'-β-hydroxyethoxyphenyl)propane, bis(4-hydroxyphenyl)sulfone, and bis(4-β-hydroxyethoxyphenyl)sulfonic acid. The aromatic diol component of the raw material that becomes the aromatic diol unit may be a derivative of an aromatic diol compound. It may also be a compound having a structure in which a plurality of aliphatic diol compounds and / or aromatic diol compounds are dehydrated and condensed with each other. The polyester resin preferably contains the above-mentioned preferred diol units in an amount of 30 mol % or more, more preferably 50 mol % or more, of the total diol units, with the upper limit being 100 mol %.
[0028] (dicarboxylic acid unit) The dicarboxylic acid unit of the polyester resin may be aliphatic or aromatic. The dicarboxylic acid unit of the polyester resin may be one type or two or more types of units in any combination and ratio, and may have an aliphatic dicarboxylic acid unit and an aromatic dicarboxylic acid unit. In terms of easy biodegradation, it is preferable to include an aliphatic dicarboxylic acid in the constituent unit. From the viewpoints of biodegradability, moldability, and mechanical strength, the number of carbon atoms in the dicarboxylic acid unit is more preferably 2 or more, and even more preferably 4 or more, while it is preferably 22 or less, more preferably 16 or less, even more preferably 13 or less, and most preferably 10 or less. The dicarboxylic acid unit is preferably a dicarboxylic acid unit represented by the following general formula (2). -OC-R 2 -CO- (2) In formula (2), R 2 represents a single bond, an aliphatic hydrocarbon group having from 1 to 20 carbon atoms, or an aromatic hydrocarbon group or heteroaromatic group having from 4 to 8 carbon atoms.
[0029] R 2 The number of carbon atoms in the aliphatic hydrocarbon group represented by the formula (I) is usually 1 or more, preferably 2 or more, more preferably 4 or more, and on the other hand, is preferably 20 or less, more preferably 16 or less, even more preferably 12 or less, and particularly preferably 8 or less. When the polyester resin contains two or more types of aliphatic dicarboxylic acid units, the combination of the aliphatic hydrocarbon groups is preferably a combination of an aliphatic hydrocarbon group having 2 carbon atoms and an aliphatic hydrocarbon group having from 4 to 10 carbon atoms.
[0030] The aliphatic dicarboxylic acid component that provides the aliphatic dicarboxylic acid unit represented by formula (2) is not particularly limited, but is preferably an aliphatic dicarboxylic acid or a derivative thereof such as an alkyl ester thereof in which the carbon number of the carboxylic acid unit containing a carboxyl group falls within the above-mentioned preferred range, and more preferably an aliphatic carboxylic acid or a derivative thereof such as an alkyl ester thereof having a carbon number of 4 to 10. Preferred aliphatic dicarboxylic acid units include, for example, oxalic acid units, malonic acid units, succinic acid units, glutaric acid units, adipic acid units, pimelic acid units, suberic acid units, azelaic acid units, sebacic acid units, brassylic acid units, undecane diacid units, and dodecane diacid units. Among these, adipic acid units, azelaic acid units, succinic acid units, and sebacic acid units are preferred, succinic acid units and sebacic acid units are more preferred, and succinic acid units are particularly preferred.
[0031] In the polyester resin, the proportion of the above-mentioned preferred dicarboxylic acid units in the total dicarboxylic acid units is preferably 5 mol% or more, more preferably 10 mol% or more, even more preferably 50 mol% or more, particularly preferably 64 mol% or more, and most preferably 68 mol% or more. The upper limit is 100 mol%. By setting the proportion of the preferred dicarboxylic acid in the polyester resin within the above range, it is possible to obtain a biodegradable resin composition that is excellent in moldability, heat resistance, and biodegradability as well. When the polyester resin contains aliphatic dicarboxylic acid units, the aliphatic dicarboxylic acid units are preferably contained in an amount of 30 mol % or more, more preferably 40 mol % or more, based on the total dicarboxylic acid units, with the upper limit being 100 mol %. When the polyester resin contains aromatic dicarboxylic acid units, the aromatic dicarboxylic acid units preferably account for 70 mol % or less, and more preferably 60 mol % or less, of the total dicarboxylic acid units.
[0032] The polyester preferably contains two or more kinds of aliphatic dicarboxylic acid components, and more preferably contains two or more kinds of the above-mentioned preferred aliphatic dicarboxylic acid components. In this case, the combination of the aliphatic dicarboxylic acid units is preferably a combination of an aliphatic dicarboxylic acid unit having 4 carbon atoms and an aliphatic dicarboxylic acid unit having 6 to 13 carbon atoms, and more preferably a combination of an aliphatic dicarboxylic acid unit having 4 carbon atoms and an aliphatic dicarboxylic acid unit having 6 to 10 carbon atoms. Specifically, the combination of the aliphatic dicarboxylic acid units is preferably at least one unit of a succinic acid unit, an adipic acid unit, an azelaic acid unit, a sebacic acid unit, and a brassylic acid unit, and more preferably a combination of two or more kinds of dicarboxylic acid units from among them.
[0033] The dicarboxylic acid unit to be combined with the succinic acid unit is preferably a pimelic acid unit, a suberic acid unit, an azelaic acid unit, an adipic acid unit, a sebacic acid unit, an undecanedioic acid unit, a brassylic acid unit or a dodecanedioic acid unit, more preferably a combination with an adipic acid unit or a sebacic acid unit, and even more preferably a combination with a sebacic acid unit. Specifically, the following polyester resins are preferred. As polyester resins having succinic acid units, polybutylene succinate (PBS), polybutylene succinate adipate (PBSA), polybutylene succinate sebacate (PBSSe) and polybutylene succinate azelate (PBSAz) are preferred, and polyester resins having two or more dicarboxylic acid units, such as polybutylene succinate adipate (PBSA), polybutylene succinate sebacate (PBSSe) and polybutylene succinate azelate (PBSAz) and polybutylene succinate brushate (PBSBr), are more preferred. As polyester resins having sebacic acid units, polybutylene succinate sebacate (PBSSe), polybutylene sebacate terephthalate (PBSeT) and polybutylene sebacate furanoate (PBSeF) are preferred. As the polyester resin having an azelaic acid unit, polybutylene succinate azelate (PBSAz), polybutylene azelate terephthalate (PBAzT), etc. are preferred. As the polyester resin having an adipic acid unit, polybutylene succinate adipate (PBSA) and polybutylene adipate terephthalate (PBAT) are preferred. As the polyester resin having a brassylic acid unit, polybutylene succinate brassylate (PBSBr) and polybutylene brassylate terephthalate (PBBrT) are preferred.
[0034] The dicarboxylic acid unit combined with the succinic acid unit is preferably contained in an amount of 5 mol% or more, more preferably 10 mol% or more, and even more preferably 15 mol% or more, based on the total dicarboxylic acid units, and more preferably 50 mol% or less, more preferably 45 mol% or less, and even more preferably 40 mol% or less. By copolymerizing an aliphatic dicarboxylic acid unit other than the succinic acid unit within the above range, the crystallinity of the polyester resin can be reduced, and the biodegradation rate can be increased.
[0035] The number of carbon atoms in the aromatic dicarboxylic acid unit represented by formula (2) is usually 4 or more and 8 or less, and preferably 6 or more. Specific examples include a 1,2-phenylene group, a 1,3-phenylene group, a 1,4-phenylene group, and a 2,5-furandiyl group.
[0036] The aromatic dicarboxylic acid component that gives the aromatic dicarboxylic acid unit represented by formula (2) is not particularly limited, but is usually an aromatic dicarboxylic acid having the above-mentioned preferred number of carbon atoms or a derivative thereof. Specifically, phthalic acid, isophthalic acid, terephthalic acid, 2,5-furandicarboxylic acid, etc. or a derivative thereof can be mentioned, among which terephthalic acid and 2,5-furandicarboxylic acid or a derivative thereof are preferred, and 2,5-furandicarboxylic acid or a derivative thereof is more preferred.
[0037] The derivative of aromatic dicarboxylic acid includes lower alkyl esters and acid anhydrides of aromatic dicarboxylic acids having 1 to 4 carbon atoms. Specific examples of the derivative of aromatic dicarboxylic acid include lower alkyl esters such as methyl esters, ethyl esters, propyl esters, and butyl esters of the above-mentioned aromatic dicarboxylic acids; cyclic acid anhydrides of aromatic dicarboxylic acids; and the like. Among them, dimethyl terephthalate is preferable. The polyester resin having dicarboxylic acid units may be a polyester resin having a different amount of dicarboxylic acid units. For example, a polyester resin containing only the above-mentioned preferred dicarboxylic acid units as dicarboxylic acid units may be blended with a polyester resin containing dicarboxylic acid units other than these, thereby adjusting the proportion of the preferred dicarboxylic acid units in the polyester resin within the above range.
[0038] <Oxycarboxylic acid unit> The polyester resin may be a resin containing an oxycarboxylic acid unit. The oxycarboxylic acid unit contained in the polyester resin is preferably an aliphatic oxycarboxylic acid unit represented by the following general formula (3). -OR 3 -CO- (3) In formula (3), R3 represents an aliphatic hydrocarbon group having 1 to 20 carbon atoms.
[0039] R 3 The aliphatic hydrocarbon group represented by the following formula (I) preferably has 16 or less carbon atoms, more preferably 12 or less carbon atoms, and further preferably 8 or less carbon atoms.
[0040] The aliphatic oxycarboxylic acid unit represented by formula (3) is not particularly limited, and examples thereof include hydroxy acid units such as lactic acid unit, glycolic acid unit, 3-hydroxybutyric acid unit, 2-hydroxy-n-butyric acid unit, 2-hydroxycaproic acid unit, 6-hydroxycaproic acid unit, 2-hydroxy-3,3-dimethylbutyric acid unit, 2-hydroxy-3-methylbutyric acid unit, 2-hydroxyisocaproic acid unit, 3-hydroxypropionic acid unit, 4-hydroxybutyric acid unit, 5-hydroxyvaleric acid unit, and 6-hydroxycaproic acid unit. These aliphatic oxycarboxylic acid units may be used as raw materials in the form of their derivatives such as lower alkyl esters or intramolecular esters. In addition, when optical isomers exist in these units, they may be either D-form or L-form. Among these, glycolic acid unit and 3-hydroxybutyric acid unit are preferred.
[0041] When the polyester resin contains these aliphatic oxycarboxylic acid units, the content is preferably 20 mol % or less, more preferably 10 mol % or less, and even more preferably 5 mol % or less, based on the total constitutional units constituting the polyester resin, from the viewpoint of moldability. The polyester resin may not contain the aliphatic oxycarboxylic acid units.
[0042] The oxycarboxylic acid unit contained in the polyester resin may contain an aromatic oxycarboxylic acid unit. Specific examples of the aromatic oxycarboxylic acid unit include p-hydroxybenzoic acid unit and p-β-hydroxyethoxybenzoic acid unit. The raw material that gives the aromatic oxycarboxylic acid unit may be a derivative of an aromatic oxycarboxylic acid compound. Alternatively, it may be a compound (oligomer) having a structure in which a plurality of aromatic oxycarboxylic acid compounds and / or aromatic oxycarboxylic acid compounds are dehydrated and condensed with each other. That is, an oligomer may be used as the raw material.
[0043] When the aromatic compound component that gives these aromatic compound units has optical isomers, any of D-isomer, L-isomer, and racemic isomer may be used. In addition, the aromatic compound component is not limited to the above examples as long as it can give aromatic compound units.
[0044] <Units with 3 or more functions> The polyester resin may be a resin having an increased melt viscosity by copolymerizing a trifunctional or higher aliphatic polyhydric alcohol with a trifunctional or higher aliphatic polycarboxylic acid or its anhydride, or a trifunctional or higher aliphatic polyoxycarboxylic acid component. When using these copolymerization components, one type may be used alone, or two or more types may be used in any combination and ratio.
[0045] Specific examples of trifunctional aliphatic polyhydric alcohols include trimethylolpropane, glycerin, etc. Specific examples of tetrafunctional aliphatic polyhydric alcohols include pentaerythritol, etc. Specific examples of trifunctional aliphatic polycarboxylic acids or their anhydrides include propanetricarboxylic acid or its anhydride, and specific examples of tetrafunctional polycarboxylic acids or their anhydrides include cyclopentanetetracarboxylic acid or its anhydride.
[0046] Trifunctional aliphatic oxycarboxylic acids are broadly classified into (i) a type having two carboxyl groups and one hydroxyl group in the same molecule, and (ii) a type having one carboxyl group and two hydroxyl groups. Either type can be used, but from the viewpoints of moldability, mechanical strength, and appearance of molded products, (i) a type having two carboxyl groups and one hydroxyl group in the same molecule, such as malic acid, is preferred, and malic acid is more preferred. In addition, the tetrafunctional aliphatic oxycarboxylic acid component is roughly classified into (i) a type in which three carboxyl groups and one hydroxyl group are shared in the same molecule, (ii) a type in which two carboxyl groups and two hydroxyl groups are shared in the same molecule, and (iii) a type in which three hydroxyl groups and one carboxyl group are shared in the same molecule. Any type can be used, but those having multiple carboxyl groups are preferred, and citric acid and tartaric acid are more preferred. These may be used alone or in any combination and ratio of two or more types.
[0047] When the polyester resin contains the above-mentioned trifunctional or higher functional component-derived structural unit, the content thereof is preferably 0.01 mol% or more as the amount contained in the total structural units constituting the polyester resin, and on the other hand, it is preferably 5 mol% or less, and more preferably 2.5 mol% or less. The polyester resin may not contain the above-mentioned trifunctional or higher functional component-derived structural unit.
[0048] <Types of polyester resin> The polyester resin contained in the resin composition according to this embodiment is preferably an aliphatic polyester resin containing aliphatic diol units and aliphatic dicarboxylic acid units as main constituent units (hereinafter, sometimes referred to as "aliphatic polyester resin (A)"); an aliphatic-aromatic polyester resin (B) in which at least a portion of the repeating units of the aliphatic polyester resin (A) are replaced with aromatic compound units; or an aromatic polyester resin (polyarylate) (C) in which the repeating units of the aliphatic polyester resin (A) are replaced with aromatic compound units, with the aliphatic polyester resin (A) being more preferred in terms of its high biodegradability.
[0049] <Aliphatic polyester resin (A)> The aliphatic polyester resin (A) is a polyester resin having an aliphatic diol unit represented by the above formula (1) and R 2 an aliphatic polyester resin containing an aliphatic dicarboxylic acid unit represented by the above formula (2), in which R is an aliphatic hydrocarbon group; 2 is an aliphatic hydrocarbon group, and the aliphatic polyester resin containing an aliphatic dicarboxylic acid unit represented by the above formula (2) and an aliphatic oxycarboxylic acid unit represented by the above formula (3) is preferred. The aliphatic diol unit represented by formula (1), R 2 The aliphatic dicarboxylic acid unit represented by formula (2) and the aliphatic oxycarboxylic acid unit represented by formula (3), in which is an aliphatic hydrocarbon group, are as described above. In addition, the aliphatic polyester resins preferred as the aliphatic polyester (A), and the aliphatic polyester resin (A) in which a trifunctional or higher aliphatic polyhydric alcohol and a trifunctional or higher aliphatic polycarboxylic acid or its acid anhydride, or a trifunctional or higher aliphatic polyoxycarboxylic acid component are copolymerized are as described above.
[0050] As the aliphatic polyester resin (A), polybutylene succinate-based resins such as polybutylene succinate (PBS), polybutylene succinate adipate (PBSA), polybutylene succinate sebacate (PBSSe), polybutylene succinate azelate (PBSAz), and polybutylene brassylate terephthalate (PBSBr) are particularly preferred because of their high biodegradability.
[0051] <Aliphatic-aromatic polyester resin (B)> The aliphatic-aromatic polyester resin (B) is a resin in which at least a part of the repeating units of the above-mentioned aliphatic polyester resin (A) is replaced with an aromatic compound unit. The aliphatic-aromatic polyester resin (B) is a resin in which at least a part of the repeating units of the above-mentioned aliphatic polyester resin (A) is replaced with an aromatic compound unit. 2aliphatic-aromatic polyester resins containing aromatic dicarboxylic acid units represented by the above formula (2), in which R is an aromatic group; 2 is an aromatic hydrocarbon group, and the aliphatic oxycarboxylic acid unit represented by formula (3) is preferably an aliphatic-aromatic polyester resin.
[0052] The aliphatic diol unit represented by formula (1), R 2 The aromatic dicarboxylic acid unit represented by formula (2) and the aliphatic oxycarboxylic acid unit represented by formula (3), in which is an aromatic hydrocarbon group, are as described above. In addition, the aliphatic polyesters preferred as the aliphatic-aromatic polyester (B) are as described above, including the case in which the aliphatic-aromatic polyester resin (B) is copolymerized with a trifunctional or higher aliphatic polyhydric alcohol and a trifunctional or higher aliphatic polycarboxylic acid or its acid anhydride, or a trifunctional or higher aliphatic polyoxycarboxylic acid component.
[0053] The aliphatic-aromatic polyester resin (B) may contain an aromatic diol unit. That is, the aliphatic-aromatic polyester resin (B) may be a polyester resin having an aromatic diol unit and an aliphatic dicarboxylic acid unit; an aromatic diol unit, an aliphatic dicarboxylic acid unit and an aromatic dicarboxylic acid unit; an aliphatic diol unit, an aromatic diol unit and an aromatic dicarboxylic acid unit; an aliphatic diol unit, an aromatic diol unit, an aliphatic dicarboxylic acid unit and an aromatic dicarboxylic acid unit. Here, specific examples of the aromatic diol component are as described above.
[0054] The aliphatic-aromatic polyester resin (B) may contain an aromatic oxycarboxylic acid unit. Specific examples of the aromatic oxycarboxylic acid component that gives the aromatic oxycarboxylic acid unit are as described above.
[0055] The aliphatic-aromatic polyester resin (B) preferably has an aromatic dicarboxylic acid unit as the aromatic unit. In this case, the content of the aromatic dicarboxylic acid unit is preferably 10 mol % or more and 80 mol % or less based on the total amount of the aliphatic dicarboxylic acid unit and the aromatic dicarboxylic acid unit (100 mol %).
[0056] As the aromatic dicarboxylic acid unit, it is preferable to use a terephthalic acid unit or a 2,5-furandicarboxylic acid unit. Specifically, the aliphatic-aromatic polyester resin (B) is preferably a polybutylene terephthalate-based resin such as polybutylene adipate terephthalate (PBAT), polybutylene succinate terephthalate (PBST), polybutylene sebacate terephthalate (PBSeT), polybutylene azelate terephthalate (PBAzT), or polybutylene brassylate terephthalate (PBBrT); or a polyfuran dicarboxylate-based resin such as polybutylene adipate furanoate (PBAF), polybutylene succinate furanoate (PBSF), polybutylene sebacate furanoate (PBSeF), polybutylene succinate sebacate furanoate (PBSSeF), polybutylene adipate sebacate furanoate (PBASeF), or polybutylene azelate furanoate (PBAzF).
[0057] As the aliphatic-aromatic polyester resin (B), a resin having a succinic acid unit, an adipic acid unit and a sebacic acid unit as a dicarboxylic acid unit is preferred.Therefore, as the aliphatic-aromatic polyester resin (B), polybutylene succinate resins such as PBST, PBSF, PBSSeF; polybutylene adipate resins such as PBAT, PBAF, PBASeF; and polybutylene sebacate resins such as PBSeT, PBSeF; PBAzT (polybutylene azelate terephthalate), PBAzF (polybutylene azelate furanoate) are preferred, and polybutylene succinate-aromatic dicarboxylic acid resins such as PBST, PBSF, PBSSeF are more preferred.
[0058] <Aromatic polyester resin (C)> The aromatic polyester resin (polyarylate) (C) is a resin in which the repeating units of the above-mentioned aliphatic polyester resin (A) are replaced with aromatic compound units. The aromatic polyester resin (C) may be a polyester resin having an aromatic diol unit and R 2 an aromatic polyester resin containing an aromatic dicarboxylic acid unit represented by the above formula (2), in which R is an aromatic hydrocarbon group; 2 is an aromatic hydrocarbon group, and an aromatic polyester resin containing an aromatic dicarboxylic acid unit represented by the above formula (2) and an aromatic oxycarboxylic acid unit which the aliphatic-aromatic polyester resin (B) may contain.
[0059] The units contained in the aromatic polyester resin (C) are as described above.
[0060] <Method of producing polyester resin> The method for producing the polyester resin can be a known method for producing polyester. The polycondensation reaction can be set under suitable conditions that have been used in the past, and is not particularly limited. The method for producing the polyester resin containing diol units and dicarboxylic acid units will be described in detail below. For polyester resins containing diol units and dicarboxylic acid units, a method is usually adopted in which, after the esterification reaction has proceeded, a reduced pressure operation is carried out to further increase the degree of polymerization.
[0061] In the case of reacting a diol component forming a diol unit with a dicarboxylic acid component forming a dicarboxylic acid unit during the production of a polyester resin, the amounts of the diol component and the dicarboxylic acid component used are adjusted so that the polyester resin produced has a target composition. Usually, the diol component and the dicarboxylic acid component react in substantially equimolar amounts, but since the diol component is distilled off during the esterification reaction, it is usually used in an excess of 1 mol % to 20 mol % over the dicarboxylic acid component.
[0062] When components such as oxycarboxylic acid units and polyfunctional component units are copolymerized with a polyester resin, the corresponding compounds (monomers or oligomers) may be reacted so that the oxycarboxylic acid units and polyfunctional component units have the desired compositions. In this case, there is no limitation on the timing and method of introducing these components into the reaction system, and they may be any as long as the polyester resin can be produced.
[0063] For example, when an oxycarboxylic acid is copolymerized into a polyester resin, the timing of introducing the oxycarboxylic acid component is not particularly limited as long as it is before the polycondensation reaction between a diol component and a dicarboxylic acid component. Examples of the timing of introducing the oxycarboxylic acid component include a method in which a catalyst is dissolved in an oxycarboxylic acid solution in advance and mixed therein, and a method in which a catalyst is introduced into the reaction system and mixed therein at the same time when the raw materials are charged.
[0064] The timing of introducing the compound that forms the polyfunctional component unit may be such that it is charged simultaneously with other monomers or oligomers at the initial stage of polymerization, or it may be charged after the ester exchange reaction and before the start of pressure reduction. From the viewpoint of process simplification, however, it is preferable to charge the compound simultaneously with other monomers or oligomers.
[0065] Polyester resins are usually produced in the presence of a catalyst. As the catalyst, any catalyst that can be used in the production of known polyester resins can be selected as long as it does not significantly impair the effects of the present invention. Examples of the catalyst include metal compounds such as germanium, titanium, zirconium, hafnium, antimony, tin, magnesium, calcium, and zinc. Among them, germanium compounds and titanium compounds are preferred.
[0066] Examples of germanium compounds that can be used as catalysts include organic germanium compounds such as tetraalkoxygermanium, and inorganic germanium compounds such as germanium oxide and germanium chloride. Among these, germanium oxide, tetraethoxygermanium, tetrabutoxygermanium, and the like are preferred from the viewpoints of price and availability, and germanium oxide is particularly preferred.
[0067] Examples of titanium compounds that can be used as catalysts include organic titanium compounds such as tetraalkoxytitanium compounds, such as tetrapropyl titanate, tetrabutyl titanate, tetraphenyl titanate, etc. Among these, tetrapropyl titanate, tetrabutyl titanate, etc. are preferred in terms of price, availability, etc.
[0068] In addition, other catalysts may be used in combination as long as the object of the present invention is not impaired. The catalysts may be used alone or in any combination and ratio of two or more.
[0069] The amount of catalyst used is arbitrary as long as it does not significantly impair the effects of the present invention, but is usually 0.0005% by weight or more, more preferably 0.001% by weight or more, and usually 3% by weight or less, preferably 1.5% by weight or less, based on the amount of monomer used. By setting the amount of catalyst within the above range, sufficient catalytic effect can be obtained while suppressing production costs, and coloration or deterioration of hydrolysis resistance of the obtained polymer can be suppressed.
[0070] The timing of introducing the catalyst is not particularly limited as long as it is before the polycondensation reaction, and it may be introduced when the raw materials are charged, or may be introduced when the pressure reduction is started. When an aliphatic oxycarboxylic acid unit is introduced, it is preferable to introduce it simultaneously with a monomer or oligomer that forms an aliphatic oxycarboxylic acid unit, such as lactic acid or glycolic acid, when the raw materials are charged, or to dissolve the catalyst in an aqueous aliphatic oxycarboxylic acid solution and introduce it, and in particular, the method of dissolving the catalyst in an aqueous aliphatic oxycarboxylic acid solution and introducing it is preferable in terms of increasing the polymerization rate.
[0071] The reaction conditions such as temperature, polymerization time, and pressure when the esterification reaction and / or transesterification reaction of the dicarboxylic acid component and the diol component are performed are arbitrary as long as they do not significantly impair the effects of the present invention. However, the reaction temperature of the esterification reaction and / or transesterification reaction of the dicarboxylic acid component and the diol component is usually 150°C or higher, preferably 180°C or higher, and on the other hand, is usually 260°C or lower, preferably 250°C or lower. The reaction atmosphere is usually an inert atmosphere such as nitrogen or argon. The reaction pressure is usually normal pressure to 10 kPa, and normal pressure is preferable. The reaction time is usually 1 hour or more, and on the other hand, is usually 10 hours or less, preferably 6 hours or less, more preferably 4 hours or less. By setting the reaction conditions within the above ranges, gelation due to excessive generation of unsaturated bonds is suppressed, and the polymerization degree can be controlled.
[0072] The pressure in the polycondensation reaction after the esterification reaction and / or transesterification reaction between the dicarboxylic acid component and the diol component is usually 0.01×10 3 Pa or more, preferably 0.03×10 3 On the other hand, it is usually 1.4 × 10 Pa or more. 3 Pa or less, preferably 0.4×10 3 It is desirable to carry out the reaction under a vacuum of 0.1 Pa or less. The reaction temperature is usually 150° C. or more, preferably 180° C. or more, and on the other hand, usually 260° C. or less, preferably 250° C. or less. The reaction time is usually 2 hours or more, and on the other hand, usually 15 hours or less, preferably 10 hours or less. By setting the reaction conditions within the above ranges, gelation due to excessive production of unsaturated bonds is suppressed, and the degree of polymerization can be controlled.
[0073] When producing the polyester resin, a chain extender such as a carbonate compound or a diisocyanate compound can also be used. In this case, the amount of the chain extender is usually 10 mol% or less, preferably 5 mol% or less, more preferably 3 mol% or less, as a ratio of carbonate bond or urethane bond to all structural units constituting the polyester resin. From the viewpoint of biodegradability of the biodegradable resin composition according to this embodiment, the carbonate bond is preferably less than 1 mol%, more preferably 0.5 mol% or less, and even more preferably 0.1 mol% or less, relative to all structural units constituting the polyester resin. The urethane bond is preferably 0.5 mol% or less, more preferably 0.3 mol% or less, even more preferably 0.12 mol% or less, and particularly preferably 0.05 mol% or less. When this amount is converted into weight % relative to the polyester resin composition, it is preferably 0.9 wt% or less, more preferably 0.5 wt% or less, even more preferably 0.2 wt% or less, and particularly preferably 0.1 wt% or less. In particular, by setting the amount of urethane bonds within the above range, smoke and odors due to decomposition of urethane bonds during the film formation process and the like are suppressed, and film breakage due to foaming in the molten film is suppressed, so that molding stability can be ensured. 1 H-NMR and 13 It can be calculated from the results of measurement using NMR (nuclear magnetic resonance spectroscopy) such as C-NMR.
[0074] Specific examples of carbonate compounds as chain extenders include diphenyl carbonate, ditolyl carbonate, bis(chlorophenyl) carbonate, m-cresyl carbonate, dinaphthyl carbonate, dimethyl carbonate, diethyl carbonate, dibutyl carbonate, ethylene carbonate, diamyl carbonate, dicyclohexyl carbonate, etc. In addition, carbonate compounds derived from hydroxy compounds such as phenols and alcohols can also be used.
[0075] Specific examples of the diisocyanate compound include known diisocyanates such as 2,4-tolylene diisocyanate, a mixture of 2,4-tolylene diisocyanate and 2,6-tolylene diisocyanate, 1,5-naphthylene diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, tetramethylxylylene diisocyanate, 2,4,6-triisopropylphenyl diisocyanate, 4,4'-diphenylmethane diisocyanate, and tolidine diisocyanate.
[0076] Other chain extenders such as dioxazoline and silicate esters may also be used. Specific examples of silicate esters include tetramethoxysilane, dimethoxydiphenylsilane, dimethoxydimethylsilane, and diphenyldihydroxysilane.
[0077] The high molecular weight polyester resins using these chain extenders (coupling agents) can also be produced using conventionally known techniques. The chain extender is usually added to the reaction system in a homogeneous molten state without a solvent after the polycondensation is completed, and reacted with the polyester obtained by the polycondensation.
[0078] More specifically, a polyester resin having a substantially hydroxyl end group, which is obtained by catalytically reacting a diol component with a dicarboxylic acid component, can be reacted with a chain extender to obtain a polyester resin having a higher molecular weight. A prepolymer having a weight average molecular weight of 20,000 or more can be produced by using a small amount of a chain extender without being affected by the remaining catalyst even under severe conditions such as a molten state, and without forming a gel during the reaction. Here, the weight average molecular weight (Mw) of the polyester resin is calculated as a monodisperse polystyrene conversion value from the measured value obtained by gel permeation chromatography (GPC) at a measurement temperature of 40°C using chloroform as a solvent.
[0079] Therefore, for example, when the polyester resin is further increased in molecular weight using the above-mentioned diisocyanate compound as a chain extender, the weight average molecular weight of the prepolymer is preferably 20,000 or more, more preferably 40,000 or more. When the weight average molecular weight is high, the amount of the diisocyanate compound used for increasing the molecular weight is small, so that the heat resistance is less likely to decrease. In this way, a polyester resin having urethane bonds having a linear structure chained via urethane bonds derived from the diisocyanate compound is produced.
[0080] The pressure during chain extension is preferably 0.01 MPa or more, more preferably 0.05 MPa or more, and even more preferably 0.07 MPa or more. On the other hand, the pressure during chain extension is preferably 1 MPa or less, more preferably 0.5 MPa or less, and even more preferably 0.3 MPa or less. And, the pressure during chain extension is most preferably normal pressure.
[0081] The reaction temperature during chain extension is preferably 100° C. or higher, more preferably 150° C. or higher, even more preferably 190° C. or higher, and particularly preferably 200° C. or higher. On the other hand, the reaction temperature during chain extension is preferably 250° C. or lower, more preferably 240° C. or lower, and even more preferably 230° C. or lower. By setting the reaction temperature within the above range, the reaction liquid is maintained at an appropriate viscosity, enabling a uniform reaction, the reaction liquid can be sufficiently stirred without requiring high stirring power, and the concurrent occurrence of gelation or decomposition of the polyester resin can be suppressed.
[0082] The time for carrying out the chain extension reaction is preferably 0.1 minutes or more, more preferably 1 minute or more, and even more preferably 5 minutes or more. On the other hand, the time for carrying out the chain extension reaction is preferably 5 hours or less, more preferably 1 hour or less, even more preferably 30 minutes or less, and particularly preferably 15 minutes or less. By setting the chain extension time within the above range, the chain can be extended to a desired molecular weight, and the concurrent occurrence of gelation or decomposition of the polyester resin can be suppressed.
[0083] <Aliphatic oxycarboxylic acid resin (D)> As the resin contained in the resin composition according to the present embodiment, an aliphatic oxycarboxylic acid resin is also preferably used. The aliphatic oxycarboxylic acid resin (D) is a resin having an aliphatic oxycarboxylic acid unit as a main constituent unit. As the aliphatic oxycarboxylic acid resin (D), for example, an aliphatic oxycarboxylic acid resin containing an aliphatic oxycarboxylic acid unit represented by the above formula (3) can be mentioned.
[0084] The aliphatic oxycarboxylic acid unit and the component that provides the unit in the aliphatic oxycarboxylic acid resin (D) are defined in the same manner as the aliphatic oxycarboxylic acid unit and the aliphatic oxycarboxylic acid component in the aliphatic polyester resin (A) described above, and preferred embodiments are also the same.
[0085] Specifically, the aliphatic oxycarboxylic acid resin (D) is preferably poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBH) or polycaprolactone (PCL), and more preferably polycaprolactone.
[0086] In addition, a urethane bond, an amide bond, a carbonate bond, an ether bond, etc. may be introduced into the aliphatic oxycarboxylic acid resin (D) so long as it does not affect biodegradability.
[0087] The method for producing the aliphatic oxycarboxylic acid resin (D) is not particularly limited, and it can be produced by a known method such as a direct polymerization method of an oxycarboxylic acid or a ring-opening polymerization method of a cyclic substance.
[0088] As the aliphatic oxycarboxylic acid resin (D), a polyhydroxyalkanoate (E) described below is preferable. <Polyhydroxyalkanoate (E)> The polyhydroxyalkanoate (E) preferably used in this embodiment is an aliphatic polyester containing a repeating unit represented by the general formula: [-CHR-CH2-CO-O-] (wherein R is an alkyl group having 1 to 15 carbon atoms), and is a copolymer containing 3-hydroxybutyrate units and 3-hydroxyhexanoate units as main constituent units.
[0089] From the viewpoint of moldability and thermal stability, the polyhydroxyalkanoate (E) preferably contains 80 mol% or more, more preferably 85 mol% or more, of 3-hydroxybutyrate units as a constituent component. In addition, the polyhydroxyalkanoate (E) is preferably produced by a microorganism. Specific examples of the polyhydroxyalkanoate (E) include poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) copolymer resin, poly(3-hydroxybutyrate-co-3-hydroxyvalerate-co-3-hydroxyhexanoate) copolymer resin, etc. In particular, from the viewpoints of molding processability and physical properties of the resulting molded article, poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) copolymer resin, ie, PHBH, is preferred.
[0090] In the polyhydroxyalkanoate (E), the composition ratio of 3-hydroxybutyrate (hereinafter sometimes referred to as 3HB) to the copolymerized comonomer such as 3-hydroxyhexanoate (hereinafter sometimes referred to as 3HH), i.e., the molar ratio of the monomers in the copolymer resin, is preferably 3-hydroxybutyrate / comonomer 97 / 3 or more, more preferably 95 / 5 or more, and on the other hand, is preferably 80 / 20 or less, more preferably 85 / 15 or less, from the viewpoint of molding processability and molded product quality. By setting the monomer ratio within the above range, the gap between the molding temperature and the thermal decomposition temperature becomes large, making molding easy, and the crystallization rate is in an appropriate range, ensuring productivity.
[0091] The ratio of each monomer in the polyhydroxyalkanoate (E) can be measured by gas chromatography as follows. 20 mg of dried polyhydroxyalkanoate is placed in a sample container, 2 ml of a sulfuric acid / methanol mixture (15 / 85 (weight ratio)) and 2 ml of chloroform are added, the container is sealed, and the polyhydroxyalkanoate is decomposed to obtain a methyl ester by heating at 100°C for 140 minutes. After cooling, 1.5 g of sodium bicarbonate is gradually added to neutralize the polyhydroxyalkanoate, and the mixture is left to stand until the generation of carbon dioxide gas stops. 4 ml of diisopropyl ether is added and mixed thoroughly, and the monomer unit composition of the sample decomposition product in the supernatant is analyzed by capillary gas chromatography to determine the ratio of each monomer in the copolymer resin.
[0092] Polyhydroxyalkanoate (E) can be produced by, for example, a microorganism such as Alcaligenes eutrophus AC32 strain, which is obtained by introducing a polyhydroxyalkanoate synthase gene derived from Aeromonas caviae into Alcaligenes eutrophus (international deposit under the Budapest Treaty, international depository authority: National Institute of Advanced Industrial Science and Technology Patent Organism Depositary Center (6-1-1 Central, Higashi 1-chome, Tsukuba City, Ibaraki Prefecture, Japan), original deposit date: August 12, 1996, transferred on August 7, 1997, deposit number FERM BP-6038 (transferred from original deposit FERM P-15786)) (J. Bacteriol., 179, 4821 (1997)).
[0093] As the polyhydroxyalkanoate (E), commercially available products can be used. Commercially available polyhydroxyalkanoates (E) containing 3-hydroxybutyrate units and 3-hydroxyhexanoate units as main constituent units include "PHBH X331N", "PHBH X131A", "PHBH X151A", "PHBH 151C" and the like manufactured by Kaneka Corporation.
[0094] In this embodiment, the aliphatic oxycarboxylic acid resin (D), including the above-mentioned polyhydroxyalkanoate (E), is not limited to one type, and two or more types of aliphatic oxycarboxylic acid resins (D) differing in the types of constituent units, the ratio of constituent units, the production method, physical properties, etc., can be blended and used.
[0095] The polyester resin contained in the resin composition according to the present embodiment may be used as each structural unit by using one type alone or two or more types in any combination and ratio. The diol unit, dicarboxylic acid unit and aliphatic oxycarboxylic acid unit may be derived from a compound derived from petroleum or from a compound derived from plant raw materials, but it is preferable to use a compound derived from plant raw materials because it is environmentally friendly.
[0096] In addition, when the aromatic compound component that gives these aromatic compound units has optical isomers, any of D-form, L-form, and racemic form may be used. In addition, the aromatic compound component is not limited to the above examples as long as it can give aromatic compound units. The aromatic compound component may be used alone or in any combination and ratio of two or more types.
[0097] (Other resins) The resin composition according to the present embodiment may contain other resins in addition to the polyester resin. The other resins are not particularly limited, and known resins can be used. For example, polyurethane resins; polyimide resins; polyacrylic resins; acrylonitrile-butadiene-styrene resins; acrylonitrile-styrene resins; polycarbonate resins; polyolefin resins such as polyethylenes such as LDPE, MDPE, HDPE, LLDPE, and carboxyl-modified polyethylene, polypropylene, polybutene, polypentene, ethylene-propylene copolymers, and ethylene-butylene copolymers; polyvinyl acetate resins; polyvinyl chloride resins; polyvinylidene chloride resins; polystyrene resins; epoxy resins; melamine resins; and polyamide resins such as nylon 6, nylon 11, nylon 66, nylon 12, nylon 610, and nylon 6T. These resins may be used alone or in combination.
[0098] When the resin composition according to the present embodiment contains other resins, particularly biodegradable resins, the biodegradable resin composition has excellent biodegradability, so that the above-mentioned preferred resins are preferably 5% by weight or more, more preferably 10% by weight or more. The resin contained in the resin composition according to the present embodiment is preferably only the above-mentioned preferred resins. However, as described above, the resin contained in the resin composition according to the present embodiment is not particularly limited as long as the biodegradability is improved by forming a resin composition with the above-mentioned enzyme carrier, and the resin may be a resin other than the above-mentioned preferred resins.
[0099] <Physical properties of resin> Reduced viscosity η of polyester resin at 30℃ sp / c may be appropriately selected depending on the application, processing method, etc. Specifically, the reduced viscosity of the resin at 30°C is preferably 0.5 dL / g or more, more preferably 0.8 dL / g or more, even more preferably 1.0 dL / g or more, and particularly preferably 1.2 dL / g or more, while it is preferably 4.0 dL / g or less, more preferably 3.0 dL / g or less, even more preferably 2.5 dL / g or less, and particularly preferably 2.3 dL / g or less. By setting the reduced viscosity of the polyester resin within the above range, it is possible to ensure the mechanical properties when processed into a molded article, and also to ensure that the melt viscosity of the resin composition during molding does not impose an excessive load on molding machines such as extruders and injection machines, thereby ensuring productivity.
[0100] The reduced viscosity of a resin can usually be measured by the following method. First, the resin is dissolved in a solvent to prepare a resin solution with a concentration c (g / dL). Next, using a capillary viscometer (Ubbelohde viscometer), the passage time t0 of the solvent and the passage time t of the resin solution are measured under a temperature condition of 30.0°C ± 0.1°C, and the relative viscosity η is calculated based on the following formula (i). rel Then, the relative viscosity η rel Based on the following formula (ii), the specific viscosity η sp Request. η rel =t / t0 (i) η sp = η rel -1 (ii) The obtained specific viscosity η sp By dividing by the concentration c (g / dL), the reduced viscosity η sp Generally, the higher this value, the larger the molecular weight.
[0101] The molecular weight of the polyester resin is usually measured by gel permeation chromatography (GPC). From the viewpoint of moldability and mechanical strength, the resin contained in the resin composition according to the present embodiment preferably has a weight average molecular weight (Mw) in the following range, using monodisperse polystyrene as the standard substance. That is, the molecular weight of the polyester resin is preferably 10,000 or more, more preferably 20,000 or more, even more preferably 30,000 or more, and particularly preferably 50,000 or more. On the other hand, it is preferably 2,500,000 or less, more preferably 1,000,000 or less, even more preferably 800,000 or less, particularly preferably 600,000 or less, particularly preferably 500,000 or less, and most preferably 400,000 or less.
[0102] In particular, the weight average molecular weight (Mw) of the polyhydroxyalkanoate resin is preferably 200,000 or more, more preferably 250,000 or more, and even more preferably 300,000 or more. On the other hand, the weight average molecular weight (Mw) of the polyhydroxyalkanoate resin is preferably 2,500,000 or less, more preferably 2,000,000 or less, and even more preferably 1,000,000 or less.
[0103] The melt flow rate (MFR) of the polyester resin can be evaluated based on JIS K 7210 (1999) at 190°C and a load of 2.16 kg. The MFR of the polyester resin contained in the resin composition according to the present embodiment is preferably in the following range from the viewpoint of moldability and mechanical strength. That is, it is preferably 0.1 g / 10 min or more, and more preferably 1 g / 10 min or more. On the other hand, the MFR of the resin is preferably 100 g / 10 min or less, more preferably 80 g / 10 min or less, even more preferably 50 g / 10 min or less, particularly preferably 40 g / 10 min or less, and most preferably 30 g / 10 min or less. The MFR of the resin can be adjusted by the molecular weight, etc.
[0104] By setting the melting point of the polyester resin within the following range, good moldability can be ensured. That is, the melting point of the polyester resin is preferably 50°C or higher, more preferably 70°C or higher, even more preferably 75°C or higher, and particularly preferably 80°C or higher, and on the other hand, it is preferably 270°C or lower, more preferably 200°C or lower, even more preferably 160°C or lower, particularly preferably 150°C or lower, especially preferably 140°C or lower, and most preferably 130°C or lower. In addition, when the polyester resin has multiple melting points, it is preferable that at least one of the melting points is within the above range.
[0105] In particular, the melting point of the polyhydroxyalkanoate resin is preferably 100°C or higher, more preferably 110°C or higher, while it is preferably 180°C or lower, more preferably 170°C or lower, and particularly preferably lower than 160°C.
[0106] The tensile modulus of the polyester resin is preferably 50 MPa or more, more preferably 100 MPa or more, in order to ensure good moldability and impact strength, and is preferably 2000 MPa or less, more preferably 500 MPa or less. The tensile modulus can be measured by the following method. A heat-pressed resin sheet is prepared and punched into a No. 8 dumbbell shape to prepare a test piece. Specifically, a metal frame (SUS304, outer diameter 110 mm, inner diameter 70 mm, thickness 0.2 mm) with a release surface treatment is placed on a PTFE tape of 150 mm x 150 mm, 1.6 g of resin is measured and taken inside the metal frame, and a PTFE tape of 150 mm x 150 mm is placed on top of it. The resin sandwiched between the PTFE tape is sandwiched between two iron plates (160 mm x 160 mm, thickness 3 mm) and heat-pressed using a heat press machine, followed by cold pressing using a cooling press machine to obtain a heat-pressed sheet of 70 mm x 70 mm x thickness 0.2 mm. The heat press temperature is 180 ° C, and the heat press time is 2 minutes for preheating and 2 minutes for pressing. The cold press temperature is 20 ° C, and the cold press time is 2 minutes. This heat-pressed sheet is uniaxially stretched at a speed of 50 mm / min, and the initial gradient of the resulting stress-strain curve is determined as the tensile modulus. The method for adjusting the melting point and tensile modulus of the polyester resin is not particularly limited, and they can be adjusted by the types of copolymerization components and their copolymerization ratios.
[0107] When the temperature of a resin is higher than the glass transition temperature, the molecular chain becomes more mobile. When a resin is biodegraded, the glass transition temperature is lower than the temperature of the environment in which the resin is placed, such as in the ocean, and this loosens the crystal structure of the resin, allowing the molecular main chain to rotate and vibrate, which is thought to facilitate biodegradation. For this reason, it is presumed that a resin with a low glass transition temperature is more likely to be biodegraded. In particular, if the glass transition temperature of a resin is 40°C or lower, it is thought that the resin is more likely to be biodegraded by the enzyme released from the enzyme carrier in seawater. Therefore, the glass transition temperature (Tg) of the polyester resin is preferably 40°C or lower, more preferably 30°C or lower, even more preferably 25°C or lower, and particularly preferably 20°C or lower. The glass transition temperature can be measured by the following method. 10 mg of resin is placed in an aluminum sample container to be used as a measurement sample. Next, a DSC is used to raise the temperature at a rate of 10°C / min under a nitrogen atmosphere to obtain a DSC chart. The glass transition temperature is determined from the baseline shift that exists on the lower temperature side of the peak indicating the melting point in this chart. Specifically, the intersection of the baseline on the lower temperature side and the inflection point is taken as the glass transition temperature.
[0108] The acid value of the polyester resin is preferably low in order to prevent hydrolysis and to provide excellent storage stability. Specifically, the acid value is preferably 250 eq / t or less, more preferably 150 eq / t or less, even more preferably 100 eq / t or less, and particularly preferably 50 eq / t or less. The acid value can be measured by the following method. Weigh out 0.4 g of resin, add 25 mL of benzyl alcohol, and dissolve by heating to 195°C and stirring. Once the resin is dissolved, cool the container containing the resin solution in an ice bath and add 2 mL of ethanol to the container. Titrate using a 0.01 N solution of sodium hydroxide in benzyl alcohol (the titration amount is A (ml)). Next, the same measurement was carried out using only benzyl alcohol to obtain the blank value (B (ml)). The acid value was calculated using the following formula. Terminal acid value (μeq / g)=(AB)×F×10 / W A (ml): Measured titer amount B (ml): Blank titration volume F: 0.01N NaOH benzyl alcohol your factor W(g): Sample weight
[0109] [Other ingredients] The resin composition according to the present embodiment may contain other components such as various additives such as fillers, plasticizers, antistatic agents, antioxidants, light stabilizers, ultraviolet absorbers, dyes, pigments, hydrolysis inhibitors, crystal nucleating agents, antiblocking agents, weather resistance agents, heat stabilizers, flame retardants, release agents, antifogging agents, surface wetting improvers, incineration aids, dispersion aids, various surfactants, slip agents, freshness retaining agents, antibacterial agents, etc., as long as the effects of the present invention are not significantly impaired. When these components are contained, the components may contain only one type, or two or more types.
[0110] When other components are contained in the resin composition, the content of the other components is preferably 40% by weight or less, more preferably 20% by weight or less, even more preferably 10% by weight or less, and particularly preferably 5% by weight or less, based on the total amount of the resin composition, from the viewpoint of not impairing the properties of the resin composition. The lower limit of the content of the other components is not particularly limited.
[0111] [Method of producing resin composition] The method for producing the resin composition according to the present embodiment is not particularly limited. The resin composition according to the present embodiment is obtained by blending a polyester resin, an enzyme carrier, and other resins and other components as necessary. The resin composition can be produced, for example, by blending each component at a predetermined ratio simultaneously or in any order, and mixing or kneading with a mixer such as a tumbler, a V-type blender, a Nauta mixer, a Banbury mixer, a kneading roll, or an extruder, preferably melt kneading. Alternatively, the resin composition can be produced by dissolving or dispersing the polyester resin and the enzyme carrier in a solvent and removing the solvent.
[0112] From the viewpoint of improving the biodegradability and biodegradation rate of the resin composition, particularly the initial biodegradation rate, it is preferable that the enzyme carrier is uniformly dispersed in the resin composition. Therefore, the resin composition is preferably produced by kneading, more preferably by melt kneading.
[0113] The kneader used for kneading may be a melt kneader. The extruder may be either a twin screw extruder or a single screw extruder, with a twin screw extruder being more preferred.
[0114] When melt-kneading is performed, the melt-kneading temperature is preferably 80° C. or higher, more preferably 100° C. or higher, and on the other hand, preferably 220° C. or lower, more preferably 210° C. or lower. Within this temperature range, melt-kneading can be performed in a short time, deterioration of the resin and deterioration of color tone are unlikely to occur, and a resin composition having better physical properties in practical aspects, such as impact resistance and moist heat resistance, is likely to be obtained. The melt-kneading time is not particularly limited as long as the enzyme carrier can be uniformly dispersed in the resin, but it is also desirable to perform the melt-kneading for a short time so as to prevent deterioration of the resin, etc. Specifically, the melt-kneading time is preferably 10 seconds or more, more preferably 30 seconds or more, and on the other hand, preferably 20 minutes or less, more preferably 15 minutes or less.
[0115] [Biodegradability of resin composition] The resin composition according to the present embodiment is preferably biodegradable. The resin composition of the present invention is particularly preferably biodegradable in seawater, where resins are considered to be difficult to biodegrade (marine biodegradable resin composition). In this specification, the degree of biodegradation is calculated as the ratio of biological oxygen demand (BOD) to theoretical oxygen demand (ThOD). For example, biodegradation in seawater is measured according to ISO 14851:1999 (Plastics - Determination of the ultimate degree of aerobic biodegradation in aqueous medium - Method by measurement of the amount of carbon dioxide evolved); biodegradation in soil is measured according to ISO 17556:2003 (Plastics - Determination of the ultimate degree of aerobic biodegradation in soil by measurement of oxygen consumption or carbon dioxide evolved using a respirometer).
[0116] [Molded body] The resin composition according to the present embodiment can be molded by various molding methods applied to general-purpose plastics. Examples of molding methods include compression molding (compression molding, lamination molding, stampable molding), injection molding, extrusion molding, co-extrusion molding (film molding by inflation method or T-die method, laminate molding, pipe molding, electric wire / cable molding, molding of profiled materials), heat press molding, hollow molding (various blow moldings), calendar molding, solid molding (uniaxial stretch molding, biaxial stretch molding, roll rolling molding, stretch-oriented nonwoven fabric molding), thermoforming (vacuum molding, compressed air molding), plastic processing, powder molding (rotational molding), various nonwoven fabric molding (dry method, adhesion method, entanglement method, spunbond method, etc.), etc. Among them, injection molding, extrusion molding, compression molding, or heat press molding is preferably applied, and injection molding or extrusion molding is more preferably applied. As a specific shape, application to a sheet, film, or container is preferable. A molded article of any of the above-described resin compositions is also preferred.
[0117] In addition, the molded article of the resin composition according to the present embodiment may be subjected to various secondary processing steps in order to impart surface functions such as chemical functions, electrical functions, magnetic functions, mechanical functions, friction / wear / lubrication functions, optical functions, thermal functions, and biocompatibility. Examples of the secondary processing steps include embossing, painting, adhesion, printing, metallizing (plating, etc.), machining, and surface treatments (antistatic treatment, corona discharge treatment, plasma treatment, photochromism treatment, physical vapor deposition, chemical vapor deposition, coating, etc.).
[0118] [Application] The resin composition according to the present embodiment is suitably used in a wide range of applications, such as packaging materials for packaging liquids, powders, solids, etc., such as various foods, medicines, and miscellaneous goods, agricultural materials, and construction materials. Specific applications include injection molded articles (for example, fresh food trays, fast food containers, coffee capsule containers, cutlery, outdoor leisure products, etc.), extrusion molded articles (for example, films, sheets, fishing lines, fishing nets, vegetation nets, secondary processing sheets, water-retaining sheets, etc.), and hollow molded articles (bottles, etc.). Further examples include agricultural films, coating materials, fertilizer coating materials, seedling pots, laminated films, plates, stretched sheets, monofilaments, nonwoven fabrics, flat yarns, staples, crimped fibers, striped tapes, split yarns, composite fibers, blown bottles, shopping bags, garbage bags, compost bags, cosmetic containers, detergent containers, bleach containers, ropes, binding materials, sanitary cover stock materials, cooler boxes, cushioning films, multifilaments, synthetic papers, and medical applications such as surgical threads, sutures, artificial bones, artificial skin, DDS such as microcapsules, wound dressings, etc. The molded articles are particularly suitable as food containers such as food packaging films, fresh food trays, fast food containers, and lunch boxes. EXAMPLES
[0119] The present invention will be described in more detail below using examples and comparative examples. The present invention is not limited by the following examples as long as it does not exceed the gist of the invention. The values of various manufacturing conditions or evaluation results in the following examples are meant as preferred upper or lower limit values in the embodiment of the present invention, and the preferred range may be a range defined by a combination of the above-mentioned upper or lower limit values and the values of the following examples or values between the examples.
[0120] <Evaluation method> (Enzyme adsorption rate) An enzyme aqueous solution with a concentration of 0.05% by weight was prepared. The absorbance of the enzyme in the enzyme aqueous solution was measured using a UV measuring device (initial concentration C0). The absorbance at 280 nm, where absorption due to aromatic amino acids is observed, was used. Next, a support was added to the enzyme aqueous solution, and the enzyme was adsorbed onto the support. The absorbance of the enzyme in the enzyme aqueous solution after adsorption was measured (post-adsorption concentration C0). IE ) Since the absorbance is proportional to the enzyme concentration, the initial concentration C0 and the concentration after adsorption C IE The adsorption rate of the enzyme to the support was calculated from the change in absorbance before and after the addition of the support. The adsorption rate can be calculated using the following formula: [(C0-C IE ) / C0]×100 For UV measurement, a UV-visible spectrophotometer "UV2600" manufactured by Shimadzu Corporation was used. In addition, in Comparative Example 1, an enzyme carrier on which the enzyme was already immobilized was purchased and used (N435, manufactured by Sigma-Aldrich), and therefore "-" is entered in the table.
[0121] (Enzyme desorption test) The enzyme carriers prepared in each Example and Comparative Example were immersed in pure water, 3.5% by weight salt water, and natural seawater at 23°C for at least 1 hour, and the degree of enzyme desorption was calculated by UV measurement in the same manner as the above-mentioned method for calculating the enzyme adsorption rate. Natural seawater was used from Mishou Bay, Ainan Town, Ehime Prefecture, and Tokyo Bay, Ota Ward, Tokyo.
[0122] (Isoelectric point of the enzyme) The isoelectric point of the enzyme was determined using precast gels (SERVAGel TM It can be measured by IEF (isoelectric focusing) 3-10 SERVA Electrophoresis (Heidelberg). The isoelectric point can be calculated visually using the SERVA IEF Marker 3-10 mixture.
[0123] (Preparation of resin composition) The crushed resin and the dried enzyme carrier were blended in the ratio shown in Table 2, put into a small twin-screw kneader (DSM's "Xplore MC15HT Micro Compounder"), and melt-kneaded for 3 minutes at 120°C under a nitrogen atmosphere. The kneaded product was crushed to a particle size (sieving method) of 250 μm or less to obtain a resin composition. Alternatively, the kneaded product was pressed into a film having a thickness of about 100 μm using a mini test press MP-WNH manufactured by Toyo Seiki Co., Ltd.
[0124] (Biodegradation evaluation) The biodegradability of the obtained resin or resin composition was measured in accordance with ISO 14851:1999 as follows. 100 mL of a mixture of a standard test culture medium prepared according to a method conforming to ISO 14851:1999 and seawater (natural seawater collected from Ainan Town, Ehime Prefecture or Tokyo Bay) was added to a 510 mL brown bottle containing 30 mg of sample. A pressure sensor (WTW, OxiTop (registered trademark)-C type) was attached to the brown bottle, and the test liquid was stirred with a stirrer for 30 days in a constant temperature environment of 25 ° C., and the biodegradability (%) based on the BOD measurement was calculated. The biodegradability of each of the reference resins PBSSe or PBSA, and the PBSSe resin composition and the PBSA resin composition containing the enzyme carrier such as Example 2 and Comparative Example 2 described later were measured, and the improvement in biodegradability of the PBSSe and PBSA resin compositions containing the enzyme carrier relative to the PBSSe resin or PBSA resin was calculated. When a is the standard resin biodegradability and b is the enzyme carrier-containing resin biodegradability, the improvement in biodegradability is calculated as b / a.
[0125] (Biodegradability evaluation, disintegration test) In addition to the BOD test, a disintegration test was carried out to evaluate the biodegradability of the obtained resin composition press film. The biodegradability of the obtained resin composition press film was evaluated as follows. The weight of the pressed film cut to approximately 1 cm x 1 cm was measured. The pressed film was placed in a 15 ml Falcon tube. Seawater collected from Tokyo Bay was filtered through an 11 μm filter. 5 ml of this seawater was poured into the Falcon tube. The pressed film cut to a specified size was immersed in seawater. The Falcon tube was placed in a Taitec Personal H-10 tabletop thermostatic shaking bath and shaken at 30°C and 60 rpm. After a specified time had passed, the pressed film was removed from the Falcon tube, and the weight of the pressed film was measured after removing the seawater adhering to the surface. Biodegradability was evaluated based on the weight retention rate relative to the initial pressed film weight.
[0126] <Polyester resin> (PBSSe) 1,4-butanediol (100.1 g), succinic acid (75.0 g), sebacic acid (32.1 g), trimethylolpropane (0.34 g), and titanium tetrabutoxide (0.50 g) were heated under nitrogen at 200°C for 2 hours with stirring. The temperature was then increased to 250°C while reducing the pressure, and the reaction was continued for 5 hours and 15 minutes. The polymer obtained was extracted into water in the form of a strand, and cut to obtain pellets of PBSSe. The reduced viscosity of PBSSe was measured according to the following measurement method, and was found to be 1.8 dL / g. The glass transition temperature was -30°C, and the acid value was 28 eq / t, each of which was measured according to the following measurement method. 1 The molar ratio of succinic acid units / sebacic acid units determined by 1 H-NMR (nuclear magnetic resonance spectroscopy) was 80 / 20. (PBSA) The reduced viscosity of PBSA of BioPBS (registered trademark) FD92PB (manufactured by PTT MCC Biochem) was measured according to the following measurement method, and was found to be 2.3 dL / g. The glass transition temperature and acid value, each of which was measured according to the following measurement method, were found to be -40°C and 29 eq / t, respectively.
[0127] (Method of measuring reduced viscosity) A resin solution was prepared by dissolving the resin in a 1:1 (weight ratio) mixed solvent of phenol and tetrachloroethane to a concentration of 0.5 g / dL. The reduced viscosity of the resin solution at 30°C was then measured using an Ubbelohde viscometer, and the reduced viscosity was calculated based on the results.
[0128] (Method of measuring glass transition temperature) 10 mg of each resin was placed in an aluminum sample container to prepare a measurement sample. Next, using a Hitachi High-Tech Science Corporation "DSC6220", the temperature was raised from -100°C to 160°C at a rate of 10°C / min under a nitrogen atmosphere to obtain a DSC chart. The glass transition temperature was determined from the baseline shift present on the lower temperature side of the peak indicating the melting point in this chart. Specifically, the intersection of the tangent point of the baseline on the lower temperature side and the inflection point was taken as the glass transition temperature.
[0129] (Method of measuring acid value) Titration was performed using the automatic titration device "GT100" manufactured by Iwate Toa DKK Co., Ltd. using the method described above.
[0130] Example 1 The enzyme used was an anionic enzyme Candida Antarctica derived lipase B (CALB) manufactured by STREM CHEMICALS, and the support was cationic cellulose Cellufine MAX Q-h (manufactured by JNC Corporation), and the enzyme was adsorbed onto the support. The adsorption method was performed by immersing the support in an aqueous enzyme solution. The enzyme concentration in the aqueous enzyme solution was 0.05% by weight, the adsorption temperature was 23°C, and the adsorption time was 6 hours or more. The isoelectric point (pI) of the enzyme was 5.2. The aqueous enzyme solution was filtered, and the residue was dried to obtain an enzyme support. The enzyme support thus prepared was subjected to a desorption test by the above-mentioned method, and the results are shown in Table 1.
[0131] Example 2 The enzyme carrier prepared in Example 1 was mixed with PBSSe at a ratio of 5% by weight to obtain a powder kneaded product, and the biodegradability was evaluated. The results are shown in Table 2.
[0132] Example 3 The enzyme was adsorbed onto the support by using an anionic enzyme Novozym (registered trademark) 51032 manufactured by Novozym as the enzyme and cationic cellulose Cellufine MAX Q-h (manufactured by JNC Corporation) as the support. The adsorption was performed by immersing the support in an aqueous enzyme solution. The enzyme concentration in the aqueous enzyme solution was 0.05% by weight, the adsorption temperature was 23°C, and the adsorption time was 6 hours or more. The isoelectric point (pI) of the enzyme was 4.3. The aqueous enzyme solution was filtered, and the residue was dried to obtain an enzyme support. The enzyme support thus prepared was subjected to a desorption test by the above-mentioned method, and the results are shown in Table 1.
[0133] Example 4 The enzyme carrier prepared in Example 3 was mixed with PBSA at a ratio of 3% by weight to obtain a powder kneaded product, and the biodegradability was evaluated. The results are shown in Table 2.
[0134] Example 5 The enzyme carrier prepared in Example 3 was mixed in PBSSe at a ratio of 1% by weight to prepare a press film of the kneaded material, and the biodegradability was evaluated. The results are shown in Table 2.
[0135] Example 6 The enzyme carrier prepared in Example 3 was mixed in a proportion of 3% by weight with PBSSe to prepare a press film of the kneaded material, and the biodegradability was evaluated. The results are shown in Table 2.
[0136] Example 7 The enzyme carrier prepared in Example 3 was mixed in PBSA at a ratio of 1% by weight to prepare a press film of the kneaded material, and the biodegradability was evaluated. The results are shown in Table 2.
[0137] Example 8 The enzyme carrier prepared in Example 3 was mixed in PBSA at a ratio of 3% by weight to prepare a press film of the kneaded material, and the biodegradability was evaluated. The results are shown in Table 2.
[0138] Example 9 The enzyme carrier prepared in Example 1 was mixed in PBSA at a ratio of 1% by weight to prepare a press film of the kneaded material, and the biodegradability was evaluated. The results are shown in Table 2.
[0139] Example 10 The enzyme carrier prepared in Example 1 was mixed in PBSA at a ratio of 3% by weight to prepare a press film of the kneaded material, and the biodegradability was evaluated. The results are shown in Table 2.
[0140] Example 11 A disintegration test was carried out on a pressed film of the kneaded material in which the enzyme carrier prepared in Example 3 was mixed in PBSA at a ratio of 1% by weight. The results are shown in Table 3.
[0141] Example 12 A disintegration test was carried out on a pressed film of the kneaded material obtained by mixing the enzyme carrier prepared in Example 3 with PBSA at a ratio of 3% by weight. The results are shown in Table 3.
[0142] Example 13 A disintegration test was carried out on a pressed film of the kneaded material obtained by mixing the enzyme carrier prepared in Example 1 in PBSA at a ratio of 3% by weight. The results are shown in Table 3.
[0143] Comparative Example 1 Novozym 435 (N435, manufactured by Sigma-Aldrich) was used as the enzyme carrier (a porous acrylic carrier (Lewatit VP OC 1600, manufactured by Laness) that does not have ionic functional groups is used as the carrier, and an anionic enzyme (CALB) is encapsulated as the enzyme. The enzyme CALB and the carrier Lewatit VP OC 1600 are not adsorbed by non-covalent bonds). The results of evaluation in the same manner as in Example 1 are shown in Table 1.
[0144] Comparative Example 2 A kneaded body was obtained in the same manner as in Example 2, except for using the enzyme carrier of Comparative Example 1. The evaluation results are shown in Table 2, similarly to Example 2.
[0145] Comparative Example 3 The PBSA pressed film containing no enzyme carrier was subjected to a disintegration test, and the results are shown in Table 3.
[0146] [Table 1]
[0147] [Table 2]
[0148] [Table 3]
[0149] As shown in Table 1, the hydrolase release rate from the support Cellufine Max Qh is higher for cutinase Novozym 51032 than for lipase CALB. Therefore, when comparing the same support loading amount of 3% (Examples 12 and 13), it is considered that the biodegradability of the support supporting Novozym 51032 was improved and the weight retention rate was decreased. [Industrial Applicability]
[0150] According to the present invention, it is possible to provide a resin composition and a molded article thereof which exhibit the function of a polymer during use as a molded article or the like, and which initiates decomposition of the polymer when exposed to an ionic aqueous solution after disposal. That is, the molded article of the present invention will not decompose even if it comes into contact with water during normal use, and can be recycled as necessary. On the other hand, if the molded article of the present invention is unintentionally disposed of in the ocean and comes into contact with seawater, it will start to decompose. Therefore, the present invention is a technology that is expected to solve the problem of marine pollution caused by plastic discarded in the ocean, and is a technology of great industrial value.
Claims
1. A resin composition comprising at least one enzyme, at least one support, and at least one resin, the resin composition containing an enzyme support in which the enzyme is adsorbed onto the support by a non-covalent bond.
2. 2. The resin composition according to claim 1, wherein the support has one or more ionic functional groups, and the enzyme is adsorbed on the support by an ionic bond.
3. The resin composition according to claim 1, wherein the enzyme carrier is contained in the resin composition in an amount of 0.5% by weight to 50% by weight.
4. The resin composition according to claim 1 , wherein the support has a cationic functional group.
5. The resin composition according to claim 1 , wherein the support has an ammonium group.
6. The resin composition according to claim 1 , wherein the support is biodegradable.
7. The resin composition according to claim 1 , wherein the enzyme has an isoelectric point of 7.0 or less.
8. The resin composition according to claim 1 , wherein the enzyme is a hydrolase.
9. The resin composition according to claim 8 , wherein the hydrolase is an esterase.
10. The resin composition according to claim 8 , wherein the hydrolase is cutinase or lipase.
11. The resin composition according to claim 1 , wherein the support contains a naturally occurring material as a constituent component.
12. The resin composition according to claim 1 , wherein the support contains either cellulose or chitosan.
13. The resin composition according to claim 1 , wherein the resin is a biodegradable resin.
14. The resin composition according to claim 13, wherein the biodegradable resin is a polyester resin.
15. The resin composition according to claim 14 , wherein the polyester resin comprises an aliphatic diol unit.
16. The resin composition according to claim 14 , wherein the polyester resin comprises an aliphatic dicarboxylic acid unit.
17. A molded article of the resin composition according to any one of claims 1 to 16.